2004
DOI: 10.1177/154405910408300216
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of RANKL and Osteoprotegerin in Gingival Crevicular Fluid of Patients with Periodontitis

Abstract: GCF, gingival crevicular fluid; IL, interleukin; OPG, osteoprotegerin; RANKL, receptor activator for NF-kappaB ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
243
5
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(290 citation statements)
references
References 20 publications
33
243
5
9
Order By: Relevance
“…The relative RANKL/OPG expression ratio is a measure of clinical relevance, its local increase in the tissues is associated with the occurrence of periodontitis [10,11,25]. In the present experimental system, the RANKL/OPG ratio was also calculated, as an indicator of the cells' capacity to enhance osteoclastogenesis and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The relative RANKL/OPG expression ratio is a measure of clinical relevance, its local increase in the tissues is associated with the occurrence of periodontitis [10,11,25]. In the present experimental system, the RANKL/OPG ratio was also calculated, as an indicator of the cells' capacity to enhance osteoclastogenesis and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CDT of A. actinomycetemcomitans regulates the expression of receptor activator of NF-kB ligand (RANKL) and osteoprotegerin by periodontal ligament cells (Belibasakis et al, 2005). Since expression of these molecules is involved in osteoclast differentiation, they have a central role in the regulation of bone resorption, a key component of periodontitis (Liu et al, 2003;Mogi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros actuales resultados son concordantes con hallazgos previos de nuestro grupo de investigación y con resultados descritos por Mogi y colaboradores, que establecen mayores niveles de RANKL en el fluido gingival crevicular (FGC) de individuos con periodontitis, con niveles de severidad de enfermedad leve, moderada y avanzada, en comparación con sujetos sin enfermedad periodontal 34,35 . En nuestros datos, no encontramos asociación significativa entre los niveles de pacientes con periodontitis mostraron niveles detectables de mARN de RANKL y estos fueron significativamente mayores que los encontrados en sujetos controles sanos.…”
Section: Papel De Los Linfocitos T Cd4unclassified